2014
DOI: 10.1080/14330237.2014.906084
|View full text |Cite
|
Sign up to set email alerts
|

Sense of meaning and study perseverance and completion: a brief report

Abstract: The study examines sense of meaning influences on study perseverance and course completion among students within a faculty of management sciences at a South African university (n = 40). Participants were selected for high scores on the Purpose in life (PIL) scale (n = 20; 50%) and contrasting low scores on the same (n = 20; 50%) (age range = 27 to 30 years, females = 73%, majority ethnicity = 70% Sotho speaking). Data were analysed using independent-samples t-test group comparison procedure. The results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Moreover, a significant link between purpose in life and parents as a resource has also been found. Makola (2014) continued the previous study by examining whether students who have a higher sense of meaning are more likely to persevere and continue with their studies compared with those who have lower sense of meaning. Participants were composed of two groups (20 students with a high Purpose in Life score and 20 students with a low Purpose in Life score) randomly selected from the 101 students who participated in the previous study.…”
Section: Meaning In Life Outcomesmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, a significant link between purpose in life and parents as a resource has also been found. Makola (2014) continued the previous study by examining whether students who have a higher sense of meaning are more likely to persevere and continue with their studies compared with those who have lower sense of meaning. Participants were composed of two groups (20 students with a high Purpose in Life score and 20 students with a low Purpose in Life score) randomly selected from the 101 students who participated in the previous study.…”
Section: Meaning In Life Outcomesmentioning
confidence: 89%
“…Moreover, it has also been found that a high sense of meaning enables students to persevere and complete their studies (Makola, 2014) and can significantly predict academic performance among college students (Mason, 2017; Makola, 2007). These existing literature suggests that meaning in life is beneficial to youth development (Navarez, 2017), and it is the salience of having meaning in life among college students that paved the way for empirical studies to examine what might contribute to having this sense of meaning.…”
Section: Introductionmentioning
confidence: 99%
“…It illustrates how individuals consistently pursue learning goals despite various challenges and difficulties ( Steger et al, 2008 ; Hill et al, 2016 ). Individuals who have a higher level of meaning in life are rarely suffering existential frustration and psychological problems ( Makola, 2014 ). Previous evidence reported that having meaning in life makes a difference in one’s cognition and behaviors and is closely linked to positive outcomes, such as self-esteem ( Steger et al, 2006 ) and enjoyment ( Steger et al, 2006 ), and thus produces a significant influence on relevant educational outcomes (e.g., Steger et al, 2008 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A sense of PAM in life appears to be a valuable construct for HE. However, studies about meaning in life in the SAHE sector is still limited (Makola & Van den Berg, 2008a, 2008bMakola, 2014;Mason, 2014Mason, , 2017Nell, 2014). The study explored how a sense of PAM, mental health and academic performance of first-year students at a HEI enrolled for courses in management sciences with at-risk subjects related to one another.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Makola and Van den Berg (2008b) reported a significant positive relationship between first-year students' sense of PAM and their academic performance. Research demonstrated students' level of PAM as positively linked to their better adjustment to university; more effective study strategies; better class attendance; better time management; perseverance and study completion (Makola, 2014;Makola & Van den Berg, 2010). Tinto (1993) identified students' intentions and commitment as key to their perseverance and success.…”
Section: Introductionmentioning
confidence: 99%